The Influence of Ce or Mn Doping on Cu-Based Catalysts for De-NOx with NH3-SCR - Lei Jiang; Yixi Cai; Miaomiao Jin; Zengzan Zhu; Yinhuan Wang (Journal of Chemistry)
In this study, the de-NOx performance of Cu-based zeolite catalysts supported on topological structure (SSZ-13, BEA, ZSM-5) and loaded with different doses of copper (from 2 to 6 wt.%) was investigated. The preparation of copper-based catalysts adopted the incipient wetness impregnation method. To analyze the physicochemical properties of the catalysts, advanced techniques like BET, XRD, NH3-TPD, H2-TPR, and DRS UV-Vis were used. The performance tests suggested the 4Cu/SSZ-13 catalyst exhibited higher low-temperature activity and wider temperature window. Furthermore, compared with Mn-Cu/SSZ-13, the Ce-Cu/SSZ-13 catalysts exhibited better de-NOx performance.